Hemagglutinin-targeting Artificial MicroRNAs Expressed by Adenovirus Protect Mice From Different Clades of H5N1 Infection - Xinying Tang; Hongbo Zhang; Yufeng Song; Dongming Zhou; Jieru Wang (Elsevier, 2016)
Influenza virus (IV) is a continuously evolving virus that widely spreads in humans and contributes to substantial morbidity and mortality. Re-emergence of human infection with avian influenza virus H5N1 poses extra challenge to IV control. Artificial microRNA (amiRNA)-mediated RNA interference has become a powerful antiviral approach due to its high specificity and rapid effect. Here, we designed several amiRNAs targeting the hemagglutinin gene of H5N1, a major determinant of pathogenicity. Expression and delivery efficiency were enhanced by presenting functional amiRNA with chimpanzee adenovirus serotype 68 (AdC68). One amiRNA, HA-1405, significantly limited H5N1 replication in vitro and inhibited 96.7% of clade 2.3.2 replication. AdC68-conjugated HA-1405 treatment remarkably decreased different clades of H5N1 plaque formation in Madin-Darby canine kidney cells. Moreover, prophylactic administration with rAd(HA-1405) markedly alleviated clinical symptoms and reduced ≃3- to 40-folds of lung viral RNA copies against four clades of H5N1 in Institute of Cancer Research (ICR) mice. Our results further showed that rAd(HA-1405) conferred 70 and 40% immediate protection against lethal clade 2.3.2 and clade 2.3.4 H5N1 challenge, respectively. In conclusion, these data provided information that HA-targeting amiRNA delivered by AdC68 could be pursued as a potential agent for highly pathogenic avian influenza viruses prevention.